Virological Breakthrough: A Risk Factor for Loss to Followup in a Large Community-Based Cohort on Antiretroviral Therapy - Catherine Orrell; Richard Kaplan; Robin Wood; Linda-Gail Bekker (AIDS Research and Treatment)
Background. We have previously shown that 75% of individuals on antiretroviral therapy (ART) in a resource-limited setting who experienced virological breakthrough to >1000 copies/mL were resuppressed after an intensive adherence intervention. This study examines the long-term outcomes of this group in order to understand the impact of the adherence intervention over time. Methods. ART-naïve adults commencing ART between September 2002 and December 2009 were reviewed. Those who achieved suppression (<50 copies/mL) were categorised by subsequent viral load: any >1000 copies/mL (virological breakthrough) or not. Those with breakthrough were sub-categorised by following viral load into failed (VL > 1000 copies/mL) or resuppressed (VL < 1000 copies/mL). Their outcome (lost-to follow-up, death, in care on first-line therapy or in care on second-line therapy) was determined as of the 13th April 2010. Findings. 4047 ART-naïve adults commenced ART. 3086 had >2 viral loads and were included in the analysis. 2959 achieved virological suppression (96%). Thereafter 2109 (71%) remained suppressed and 850 (29%) experienced breakthrough ( (33%) failed and (67%) resuppressed). Individuals with breakthrough were younger (), had lower CD4 counts (), and higher viral loads () than those who remained suppressed. By 7 years the risk of breakthrough was 42% and of failure 15%. Fewer adults with breakthrough remain in care over time (). Loss to care is similar whether the individuals failed or resuppressed. Interpretation. While 67% of those who experience initial virological breakthrough resuppress after an adherence intervention, these individuals are significantly less likely be retained in care than those who remain virologically suppressed throughout.